Yield and nutritional responses of quinoa (Chenopodium quinoa Willd.) genotypes to irrigated, rainfed, and drought-stress environments - Pathan, Safiullah; Ndunguru, Grato; Clark, Kerry; Ayele, Addissu G. (Frontiers in Sustainable Food Systems, 2023)
This study aimed to select higher-yielding and drought-tolerant quinoa (Chenopodium quinoa Willd.) lines suitable for cultivation in the U.S. Midwest, where water scarcity poses a common challenge for crop production. Quinoa, known as a superfood and climate-smart crop, is rich in nutrients, possesses resilience to abiotic stress, and is ideal for sustainable food production and supporting nutritional security in the face of changing climate conditions. To achieve this goal, 128 quinoa germplasms, collected from the USDA-ARS-GRIN, were evaluated. Among those lines, ten quinoa lines were selected for further assessment and evaluated at four different locations in Missouri, United States. Evaluations were conducted under three environments: irrigated, rainfed, and drought stress, over 2 years (summer of 2021 and 2022). Two of the selected ten lines, Ames13746 and PI614927, produced higher yields across various locations and environments. Remarkably, these lines demonstrated significantly higher grain yields under drought stress compared to irrigated and rainfed conditions. However, there was no significant difference in grain yield between irrigated and rainfed environments. Notably, despite the presence of moisture stress, the concentration of essential amino acids remained unaffected, while there was a slight decrease in the total protein content under drought-stress conditions. These research results and selected genotypes can potentially facilitate quinoa production in the U.S. Midwest regions prone to water stress, contributing to food security and sustainable agricultural practices.